Influence of moisture source and sink regions on northeast monsoon rainfall. (11th December 2017) - Suneetha, P.; Latha, P.; Ramalingeswara Rao, S.; Bhanu Kumar, O. S. R. U.
ABSTRACT: The northeast monsoon (NEM) over south India plays a vital role in producing light and moderate rainfall events during October through December. Excess NEM rainfall is mainly due to the intensified tropical cyclones and easterly waves from the Pacific east–west troughs over the Bay of Bengal. The main heat source and sink regions of this monsoon season are the western Pacific high and the Siberian high, respectively. Relative variations in the areal extent and intensity of these source and sink regions influence the NEM season by excess or deficient rainfall. Hence, the aim of the present study was to observe the impact of the Siberian high and the western Pacific high on the NEM rainfall in excess and deficient years. For this purpose, dynamic and thermodynamic parameters, the zonal and meridional winds, the velocity potential, the sea surface temperature and the relative humidity of the National Centers for Environmental Prediction and the National Center for Atmospheric Research (NCEP/NCAR) reanalysis data were used for the period 1951–2014. Analysis of these variables revealed the importance of the source and sink regions for the enhancement/reduction of NEM rainfall during excess/deficient years. Abstract : Meteorological subdivisions of the study.